2019
DOI: 10.3390/jcm9010030
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Pituitary Adenomas

Abstract: The genetic landscape of pituitary adenomas (PAs) is diverse and many of the identified cases remain of unclear pathogenetic mechanism. Germline genetic defects account for a small percentage of all patients and may present in the context of relevant family history. Defects in AIP (mutated in Familial Isolated Pituitary Adenoma syndrome or FIPA), MEN1 (coding for menin, mutated in Multiple Endocrine Neoplasia type 1 or MEN 1), PRKAR1A (mutated in Carney complex), GPR101 (involved in X-Linked Acrogigantism or X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 151 publications
(176 reference statements)
0
29
0
9
Order By: Relevance
“…Further, genetic mutations associated with dysfunctional cAMP pathways also manifest as somatotroph adenomas at different ages. For example, familial isolated somatotroph adenomas associated with AIP mutations manifest at older ages, whereas somatotroph adenomas associated with GPR101, specifically mosaic microduplications of Xq26.3, manifest before 2 years of age (63). Although cAMP-associated mutations have not been identified in most sporadic somatotroph adenomas, several lines of evidence support the presence of cAMP pathway hyperactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, genetic mutations associated with dysfunctional cAMP pathways also manifest as somatotroph adenomas at different ages. For example, familial isolated somatotroph adenomas associated with AIP mutations manifest at older ages, whereas somatotroph adenomas associated with GPR101, specifically mosaic microduplications of Xq26.3, manifest before 2 years of age (63). Although cAMP-associated mutations have not been identified in most sporadic somatotroph adenomas, several lines of evidence support the presence of cAMP pathway hyperactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this gene were first identified in the multiple endocrine neoplasia type 1 syndrome [ 29 , 30 ]. Subsequent analysis revealed that MEN1 alterations are also found in a subset of pancreatic endocrine tumors [ 31 , 32 , 33 ] and pituitary adenomas [ 34 ], as well as several other cancers [ 35 , 36 ]. In addition to its independent function, MEN1 also interacts with the lysine methyltransferase KMT2A (previously MLL1), and this interaction contributes to the oncogenic properties of KMT2A [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carney complex was first fully characterized by J Aiden Carney in 1985 (Carney et al 1985), although earlier descriptions exist. Others have described the multiple heritable causes of primary hyperparathyroidism (Marx & Goltzman 2019), pituitary tumours (Tatsi & Stratakis 2019) and pheochromocytoma/ paraganglioma (Crona et al 2017). Beginning in the 1960s, there was the confluence of hormone discovery and characterization of clinical and genetic information that permitted the development of the current classification of MEN syndromes.…”
Section: Overviewmentioning
confidence: 99%